Research and development of effective dye composition formulations for use in the dyeing process of cotton fabric (Международный научный журнал «Инженер», 2026)
This article presents the results of studies of the process of modifying cotton fabric with fibroinoligomers, the influence of pH, temperature, concentration of polyvalent metal salts, sodium nitrite andresorcinol on the formation of metal complexes in the structure of cotton fiber, as well as the establishedoptimal compositions of the developed powder composite dyes for the production of composite dyes andfor dyeing textile cotton and viscose fabrics.